The sustainable university : progress and prospects - Sterling, Stephen R.; Maxey, Larch; Luna, Heather (London : Routledge, 2013)
"The direction of higher education is at a cross roads against a background of mounting sustainability related issues and uncertainties. This book seeks to inspire positive change in higher education by exploring the rich notion of the sustainable university and illustrating pathways through which its potential can be realised. Based on the experience of leading higher education institutes in the UK, the book outlines progress in the realisation of the concept of the sustainable university appropriate to the socio-economic and ecological conditions facing society and graduates. Written by leading exponents of sustainability and sustainability education, this book brings together examples, insight, reflection and strategies from the experience of ten universities, widely recognised as leaders in developing sustainability in Higher Education. The book thus draws on a wealth of experience to provide reflective critical analysis of barriers, achievements, strategies and potential. It critically reviews the theory and practice involved in developing the sustainable university in a systemic and whole institutional manner, including the role of organisational learning. Whilst remaining mindful of the challenges of the current climate, The Sustainable University maps out new directions and lines of research as well as offering practical advice for researchers, students and professionals in the fields of management, leadership, organisational change, strategy, and curriculum development who wish to take this work further"--
pt. I. Context -- pt. II. Aspects -- pt. III. Institutional change.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Universities and colleges -- Environmental aspects -- Great Britain; Environmental education -- Great Britain; Sustainable development -- Great Britain; Electronic books